Spirocyclopiperazinium salt compound DXL-A-24 improves visceral sensation and gut microbiota in a rat model of irritable bowel syndrome - Yan Xu; Ru Yao; Wenxue Zhao; Jianguo Zhu; Jingchun Yao; Guimin Zhang; Dongguang Liu (Heliyon, 2023)
Irritable bowel syndrome (IBS) is characterized by visceral pain, impaired intestinal barrier and a disorder of the microbiota. DXL-A-24 has analgesic and anti-inflammatory effects by inhibiting neuropeptides and inflammatory factors. In this study, we used chronic unpredictable mild stress (CUMS) induced IBS model, to assess the action of DXL-A-24 on visceral hypersensitivity, barrier function and microbiota. Visceral sensation was assessed by colorectal distension in a model of IBS. The expressions of substance P (SP) and calcitonin gene-related peptide (CGRP) were detected by immunohistochemistry and western blot, the contents of diamine oxidase (DAO) and D-lactic acid were detected by ELISA, and 16S rRNA to detect the diversity of gut microbiota. CUMS reduced visceral pain threshold and increased colonic permeability of rats. DXL-A-24 for 28 days inhibited these changes. DXL-A-24 also decreased the expression of SP, CGRP in colon and D-LA, DAO in serum. Besides, DXL-A-24 increased the richness and diversity of intestinal microbiota. In conclusions, DXL-A-24 reduced visceral sensitivity, improved intestinal barrier and regulated gut microbiota in rats with IBS.